2016
DOI: 10.1007/s11606-016-3825-9
|View full text |Cite
|
Sign up to set email alerts
|

Why Aren’t More Primary Care Residents Going into Primary Care? A Qualitative Study

Abstract: BACKGROUND:Workforce projections indicate a potential shortage of up to 31,000 adult primary care providers by the year 2025. Approximately 80 % of internal medicine residents and nearly two-thirds of primary care internal medicine residents do not plan to have a career in primary care or general internal medicine. OBJECTIVE: We aimed to explore contextual and programmatic factors within primary care residency training environments that may influence career choices. DESIGN: This was a qualitative study based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…One published work observed that status among peers was considered important by more than 40% of fourth-year medical students (Osborn, et al, 2017). In another, residents noted that there was a cultural sense that primary care medicine lacked the prestige of other specialties (Long, et al, 2016), especially by other physicians who viewed general medicine negatively. This highlights the need for mentors and faculty who not only practice primary care medicine, but who are able to convey to their students the positive aspects of pursuing primary care early on in the student's training, which can include the opportunity to impact a patient's total health by establishing a doctor-patient relationship.…”
Section: Discussionmentioning
confidence: 99%
“…One published work observed that status among peers was considered important by more than 40% of fourth-year medical students (Osborn, et al, 2017). In another, residents noted that there was a cultural sense that primary care medicine lacked the prestige of other specialties (Long, et al, 2016), especially by other physicians who viewed general medicine negatively. This highlights the need for mentors and faculty who not only practice primary care medicine, but who are able to convey to their students the positive aspects of pursuing primary care early on in the student's training, which can include the opportunity to impact a patient's total health by establishing a doctor-patient relationship.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent qualitative study examining such factors discovered that more patients seen‚ a diversity of outpatient experiences, and supportive resources that address social determinants of health all positively influence the pursuit of primary care careers among trainees. 23 Not surprisingly, scheduling models that limit inpatient and outpatient conflict for residents may translate into greater resident satisfaction with their training. 24 X + Y scheduling, a model that schedules residents' inpatient or non-ambulatory rotations (BX^blocks) in discrete periods with alternating ambulatory or BY^blocks, is instituted specifically to decrease the conflict between inpatient and outpatient patient care responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition to the single-center study design, interpretation of the findings may be confounded by institutional modifications impacting patient outcome measures. In our era of the Affordable Care Act (ACA) and the primary care crisis, 4 addressing inpatient and ambulatory training disparities is fertile ground for research and innovation. This study helps us recognize the impact of workload reduction on resident experience, but does not analyze ultimate career determinations.…”
mentioning
confidence: 99%